UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT MELALUI PROGRAM KUBE PKH DI KABUPATEN CIAMIS - Tiktiek Kurniawati; Rian Kurnia (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
KUBE-PKH is one of the programs carried out by the government in handling poverty through business groups in the form of community groups or social assisted families formed by members or social assisted families who have been fostered through the process of Social Welfare Program (PROKESOS) activities as a means of increasing the social welfare. The method in this research is to use survey research methods. Survey research is research that takes a sample from one population as a basic data collection tools. The result is that 1. Of the three Districts including Sukamantri District, Panjalu District and Rajadesa District, all of them show the results that the KUBE program that has been implemented on average has met the measure of efforts to increase community welfare. 2. The obstacles in implementing KUBE-PKH include human resources, education and economy.